Petroleum biotechnology developments and perspectives - Vazquez-Duhalt, Rafael; Quintero Ramirez, Rodolfo, 1954- (Amsterdam ; London : Elsevier, 2004)
This book is one of a kind in the field of petroleum biorefining and biological upgrade of petroleum; it presents a critical review as well as an integrated overview of the potential biochemical processes, bridging the gap between academia and industry. It addresses todays demanding production challenges, taking into account energy efficient and environmentally friendly processes, and also looks at the future possibility of implementing new refinery systems. Suitable for those practitioners the petroleum industry, students and researchers interested in petroleum biotechnology. * Covers a new application field for biotechnology * Looks at innovative processes for the petroleum industry * Presents examples of modern environmental processes.
Use of petroleum biotechnology throughout the value chain of an oil company : an integrated approach / H. Kr. Kotlar, O.G. Brakstad, S. Markussen and A. Winnberg -- Petroleum biorefining : the selective removal of sulfur, nitrogen, and metals / J.J. Kilbane II and S. Le Borgne -- Enzymatic catalysis on petroleum products / M. Ayala and R. Vazquez-Duhalt -- Prospects for biological upgrading of heavy oils and asphaltenes / K.M. Kirkwood, J.M. Foght and M.R. Gray -- Whole-cell bio-processing of aromatic compounds in crude oil and fuels / J.M. Foght -- Biocatalysis by methane monooxygenase and its implications for the petroleum industry / T.J. Smith and H. Dalton -- Biocorrosion / H.A. Videla and L.K. Herrera -- Molecular tools in microbial corrosion / X. Zhu and J.J. Kilbane II -- Potential applications of bioemulsifiers in the oil industry / H. Bach and D.L. Gutnick -- Anaerobic hydrocarbon biodegradation and the prospects for microbial enhanced energy production / J.M. Suflita, I.A. Davidova, L.M. Gieg, M. Nanny and R.C. Prince -- Using nitrate to control microbially-produced hydrogen sulfide in oil field waters / R.E. Eckford and P.M. Fedorak -- Regulation of toluene catabolic pathways and toluene efflux pump expression in bacteria of the genus Pseudomonas / J.L. Ramos, E. Duque, M.T. Gallegos, A. Segura and S. Marquβes -- Bacterial hydrocarbon biosynthesis revisited / B. Valderrama -- The microbial diversity of deep subsurface oil reservoirs / N.-K. Birkeland -- Biotechnological approach for development of microbial enhanced oil recovery technique / K. Fujiwara, Y. Sugai, N. Yazawa, K. Ohno, C.X. Hong and H. Enomoto -- Phytoremediation of hydrocarbon-contaminated soils : principles and applications / R. Kamath, J.A. Rentz, J.L. Schnoor and P.J.J. Alvarez -- Biological treatment of polluted air emissions / S. Revah and R. Auria -- Bioremediation of marine oil spills / R.C. Prince and J.R. Clark -- Biotreatment of water pollutants from the petroleum industry / E. Razo-Flores, P. Olguβin-Lora, S. Alcβantara and M. Morales-Ibarrβia.
Includes bibliographical references.
Keywords: Petroleum -- Refining; Petroleum -- Microbiology; Minerals -- Biotechnology; Electronic books